Genomic Characterization of Potential Opportunistic Zoonotic Streptococcus parasuis Isolated in China - Gang Liu; Yu Liu; Zhikang Jiang; Kang Liu; Xianwen Wang; Juyuan Hao; He Kong; Yajie Yu; Zicheng Ding; Min Li; Xianjie Han (Pathogens)
(1) Background: S. parasuis is a potential opportunistic zoonotic pathogen that can infect pigs, cattle, and humans, composed of former members of S. suis serotypes 20, 22, and 26. In recent years, unclassified serotypes and a serotype 11 S. parasuis have been discovered. (2) Methods: We characterized two S. parasuis strains (FZ1 and FZ2) isolated from brain samples of paralyzed pigs and examined evolutionary divergence among 22 available S. parasuis and 8 serotype 2 S. suis genomes through whole-genome sequencing and comparative genomic analysis. We compared virulence genes (VGs) and antibiotic resistance genes (ARGs) and analyzed mobile genetic elements (MGEs) in FZ1 and FZ2. (3) Results: Comparative genomics revealed that srtC, ctpV, and sugC may represent key virulence determinants in S. parasuis, although their pathogenic potential appears attenuated compared to serotype 2 S. suis. In addition, S. parasuis exhibited primary resistance to aminoglycosides, macrolides, tetracyclines, and oxazolidinones, while demonstrating heightened susceptibility to oxazolidinone-class antibiotics. Moreover, we found an important association between MGEs and antibiotic resistance in S. parasuis FZ1 and FZ2. (4) Conclusions: This study provides new insights into the genomic and evolutionary characteristics of S. parasuis and provides a new basis for the study of bacterial pathogenesis and drug resistance in the future.